Perbandingan Tingkat Pemahaman Siswa Terhadap Materi Pai Di Indonesia Dan Malaysia - Fatiha Fatiha; Rahmatun Nisak; Widia Ningsih; Nur Annisabela (Jurnal Ilmu Agama Indonesia, 2026)
This study aims to analyze and compare students' understanding of Islamic Religious Education (PAI) materials in Indonesia and Malaysia. The method used was qualitative research with a library research approach, through the review of various sources such as books, scientific journals, academic articles, research reports, and relevant educational policy documents. The results of the study indicate that students' understanding of PAI materials is influenced by various factors, both internal and external, such as learning motivation, individual abilities, teacher competence, learning methods, curriculum, family environment, school environment, and the use of technology. Indonesia and Malaysia share the same goal in Islamic religious education: to develop students who are faithful, pious, and have noble character. However, there are differences in the implementation of the curriculum, learning methods, and evaluation systems. Malaysia tends to adopt a more integrated approach between religious theory and practice, while Indonesia still faces several obstacles, such as limited learning time and the dominance of memorization methods. This study concludes that improving students' understanding of Islamic Religious Education (PAI) material requires innovative learning strategies, family support and a conducive environment, as well as synergy between schools, families, and the community so that students not only understand Islamic teachings theoretically, but are also able to practice them in their daily lives.